Harmonic vowels and neural dynamics: MEG evidence for auditory resonance integration in singing - Saus, Wolfgang; Seither-Preisler, Annemarie; Schneider, Peter (Frontiers in Neuroscience, 2025)
IntroductionAuditory perception of sung syllables involves rapid shifts between speech-like interpretation and spectral awareness of resonance. Perceiving vocal tract resonances as pitch-like elements may be crucial for singers, linking this concept to pedagogical practice and underlying neural mechanisms. This study examines how vowel resonance becomes accessible to conscious processing and how such perceptual shifts are reflected in neural dynamics.MethodsDrawing on a novel acoustic-phonetic model of “harmonic vowels,” we presented sung syllables that varied systematically across six distinct conditions, ranging from speech-like utterances to overtone singing. Magnetoencephalographic (MEG) recordings from 17 participants revealed distinct modulations in cortical oscillatory activity.ResultsTheta-band power (4–7 Hz) increased linearly with decreasing speech content and showed strong right-hemispheric lateralization (partial η² = 0.82), indicating a key role in the cortical representation of spectral content. Gamma-band power (30–60 Hz) declined moderately and was left-lateralized. These findings show that vowel resonance is perceptually accessible and subject to rapid auditory reorientation, reflecting neural flexibility that may underlie auditory plasticity in both trained and untrained listeners. Individual differences in pitch perception mode (fundamental vs. overtone-based), indicating a stable perceptual trait, were also systematically reflected in oscillatory patterns: overtone listeners exhibited higher theta power, lower gamma power, and stronger right-hemispheric lateralization in both bands.DiscussionTheta and gamma power were inversely correlated, suggesting complementary functions in detail-oriented spectral representations and global feature binding. The results offer novel implications for vocal pedagogy, auditory training, and sound-based therapeutic applications.